Irigenin Alleviates Blue Light‐Induced Retinal Damage by Upregulating Antioxidative Defense System via Nrf2 Pathway In Vivo and In Vitro - Yeh, Kun‐Lin; Kuan, Yu‐Hsiang; Wu, Sheng‐Wen; Chiang, Chen‐Yu; Chen, Chun‐Jung; Chen, Wen‐Ying; Chou, Chi‐Chung (Environmental toxicology, 2025)
ABSTRACT This research aimed to assess the potential of irigenin to attenuate blue light (BL)‐induced apoptosis in human adult retinal pigment epithelial (hARPE‐19) cells loaded with N‐retinylidene‐N‐retinylethanolamine (A2E, DA50062). Furthermore, the study investigated the associated molecular mechanisms. Cell viability was assessed using the MTT assay, and flow cytometry was employed to evaluate reactive oxygen species (ROS) production, alterations in mitochondrial membrane potential, and cytochrome c release. Lipid peroxidation levels, as well as the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH‐Px), and caspase enzymes, were quantified using commercially available assay kits. Bcl‐2, Bax, heme oxygenase‐1 (HO‐1), and nuclear factor erythroid 2‐related factor 2 (Nrf2) expression was quantified through western blotting. Moreover, animal experiments were performed to assess BL‐induced retinal damage. The results revealed that irigenin protected against BL‐induced cytotoxicity and apoptosis in DA50062‐laden hARPE‐19 cells. Furthermore, irigenin upregulated Bcl‐2 expression and downregulated Bax expression in BL‐exposed DA50062‐laden hARPE‐19 cells. Hence, irigenin prevented cytochrome c release and inhibited BL‐induced caspase‐3 and caspase‐9 activation in DA50062‐laden hARPE‐19 cells. Irigenin also effectively inhibited lipid peroxidation and ROS production in BL‐exposed DA50062‐laden hARPE‐19 cells. Notably, irigenin upregulated Nrf2 expression, which, in turn, upregulated the expression of several antioxidative defense system, such as SOD, CAT, and GSH‐Px, and HO‐1 in BL‐exposed DA50062‐laden hARPE‐19 cells. Animal studies showed that irigenin effectively protected against BL‐induced retinal damage, as indicated by the increased thickness of the outer and inner nuclear layers in irigenin‐treated groups compared to untreated controls. Taken together, the results suggest that irigenin inhibits the BL‐induced intrinsic apoptotic pathway by activating the Nrf2‐mediated antioxidative defense system.